An experimental investigation of association between children’s lying and behavior problems - Liu, Xue; Shang, Siyuan; Zanette, Sarah; Zhang, Yongkang; Sun, Qingzhou; Sai, Liyang (Frontiers in Psychology, 2022)
Children’s lying is a major concern for parents and teachers alike, not only because lying is an antisocial behavior but also because children’s lying correlates with other behavior problems, such as aggression and delinquency. Despite considerable correlational evidence demonstrating the relation between children’s lying and behavior problems, experimental evidence is scarce. This study uses a novel task to experimentally examine the relation between lying for personal reward and behavior problem symptoms among 9- to 11-year-old typically developed children (N=275, 139 boys). Results revealed a positive correlation between children’s lying for personal reward and their behavior problem symptoms, and this correlation increases with age. Overall, this study provides experimental evidence suggesting children’s lying for personal reward is associated with behavior problems.